Electrolyzer switching strategy for hydrogen generation from variable speed wind generator - Muyeen, S.M.; Takahashi, R.; Tamura, J. (Elsevier BV, 2011)
This paper presents a new switching strategy for electrolyzer used in hydrogen generation which is connected to the terminal of a wind farm. The output of wind generator, in general, fluctuates greatly due to the random wind speed variations, which has a serious influence on the power system operation. In this study, the wind farm is composed of variable speed wind turbines (VSWT) driving permanent magnet synchronous generators (PMSG). The hydrogen generator (HG) is composed of rectifier and 10 electrolyzer units where each unit is controlled by the chopper circuit. To smoothen the wind farm line power, at first, a reference for the line power is generated from the difference of exponential moving average of wind farm output and its standard deviation. Then the switching strategy is developed in such a way that the proposed cooperative system can smoothen the wind farm line power fluctuation as well as generating hydrogen gas absorbing the fluctuating portion of wind farm output that lies above the reference line power. This novel switching strategy helps each electrolyzer unit working in full load and shift operation conditions and hence increases its lifespan and efficiency. The performance of the proposed system is investigated by simulation analyses, in which simulations are performed by using PSCAD/EMTDC.